Program-L: Online Help Seeking Behaviors by Blind and Low Vision Programmers - Johnson, Jazette; Begel, Andrew; Ladner, Richard; Ford, Denae (IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), 2022)
Although the number of blind or low vision (BLV) software developers is the largest minority population of developers with physical disabilities, they are often marginalized in mainstream online programming communities. We studied how BLV developers engage with a BLV-specific programming community called Program-L, by exploring the help-seeking behaviors of novices. We analyzed 173 messages written by 20 novices over a 4-year period and identified the kinds of help they asked for and their justifications for requesting that help. We learned that self disclosure, practical assistance, and community dynamics were all critical activities to support four types of novices: community, domain, programming, and accessibility. The findings of our work give insight into what support can look like for online communities for marginalized software developers.